Openreuma Consensus on the role of nursing in the care of patients with rheumatoid arthritis and diffuse interstitial lung disease - Cano García, Laura; Castiblanco, Laura; Marcos Pérez, Elena; Vázquez Lojo, Ana; León Mateos, Leticia; Espíldora Hernández, Francisco; Jiménez Núñez, Francisco; Rodríguez Vargas, Ana Isabel; García-Díaz, Silvia; Domínguez Quesada, Carmen; Martín Martín, José Ma; Mena Vázquez, Natalia; et al. (Investigación y Educación en Enfermería, 2023)
Objective. To develop practical recommendations, based on the best available evidence and experience, on the nursing management of patients with rheumatoid arthritis (RA) and interstitial lung disease (ILD). Methods. The usual consensus methodology was used, with a nominal group, systematic reviews (SRs), and Delphi survey. The expert panel, consisting of rheumatology nurses, rheumatologists, a psychologist, a physiotherapist, and a patient, defined the scope, the users, the topics on which to explore the evidence and on which to issue recommendations. Results. Three PICO questions evaluated the efficacy and safety of pulmonary rehabilitation and non-pharmacological measures for the treatment of chronic cough and gastroesophageal reflux by means of SR of the literature. With the results of the reviews, 15 recommendations were established for which the degree of agreement was obtained with a Delphi survey. Three recommendations were rejected in the second round. The 12 recommendations were in patient assessment (n=4); patient education (n=4); and risk management (n=4). Only one recommendation was based on available evidence, while the remaining were based on expert opinion. The degree of agreement ranged from 77% to 100%. Conclusion. This document presents a series of recommendations with the aim of improving the prognosis and quality of life of patients with RA-ILD. Nursing knowledge and implementation of these recommendations can improve the follow-up and prognosis of patients with RA who present with ILD.